The Australian National Aged Care Classification (AN‐ACC): a new casemix classification for residential aged care. Issue 8 (27th July 2020) - Eagar, Kathy; Gordon, Rob; Snoek, Milena F; Loggie, Carol; Westera, Anita; Samsa, Peter David; Kobel, Conrad
Abstract: Objective: To develop a casemix classification to underpin a new funding model for residential aged care in Australia. Design, setting: Cross‐sectional study of resident characteristics in thirty non‐government residential aged care facilities in Melbourne, the Hunter region of New South Wales, and northern Queensland, March 2018 – June 2018. Participants: 1877 aged care residents and 1600 residential aged care staff. Main outcome measures: The Australian National Aged Care Classification (AN‐ACC), a casemix classification for residential aged care based on the attributes of aged care residents that best predict their need for care: frailty, mobility, motor function, cognition, behaviour, and technical nursing needs. Results: The AN‐ACC comprises 13 aged care resident classes reflecting differences in resource use. Apart from the class that included palliative care patients, the primary branches were defined by the capacity for mobility; further classification is based on physical capacity, cognitive function, mental health problems, and behaviour. The statistical performance of the AN‐ACC was good, as measured by the reduction in variation statistic (RIV; 0.52) and class‐specific coefficients of variation. The statistical performance and clinical acceptability of AN‐ACC compare favourably with overseas casemix models, and it is better than the current Australian aged care funding model, the Aged Care Funding Instrument (64 classes; RIV, 0.20). Conclusions: The care burden associated with frailty, mobility, function, cognition, behaviour and technical nursing needs drives residential aged care resource use. The AN‐ACC is sufficiently robust for estimating the funding and staffing requirements of residential aged care facilities in Australia.